The Utilization of Sago Dregs to Increase Body Weight Gain and Feed Conversion Rate of Balitbangtan Superior Native Chicken - Yayu Zurriyati; Salfina Nurdin Ahmad; Yenni Yusriani (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
The utilization of local resource materials as the feed source for native chicken, such as sago dregs, is a potential solution to reduce the cost of conventional chicken feed. Sago dregs is produced from sago processing that is widely available in Meranti Island Regency, Riau Province. This research was aimed to determine how much evaluate the potential of sago dregs for native chicken feed in Meranti Regency. Testing sago-dregs based ration was carried out on 80 four-week-old Balitbangtan superior native chicken in four treatments (n=20) as follows: P1 = 60% fermented sago dregs (FSD)) + 10% corn + 30% trash fish; P2 = 60% FSD + 10% coffee skin + 30% trash fish; P3 = 50% FSD + 50% commercial chicken feed; P4 = 50% non-fermented sago dregs (NFSD)) + 50% commercial chicken feed. The commercial starter was given to 0-4 weeks-old chickens, while treatment feed was given to 4-12 weeks. The parameters observed were body weight gain and feed conversion ratio. The research data obtained were processed statistically using the T-test. The results showed a significantly lower (P <0.05) average body weight of chickens in P2 (630 grams) than that of P3 (808 grams) and of P4 (806 grams). Meanwhile, the P1 chickens’ weight (722 grams) was not significantly different from the others. The feed conversion ratio of P1, P2, P3, and P4 was 3.2, 3.3, 3.1, and 3.5, respectively. Sago dregs is a potential substitute for conventional feed for Balitbangtan's superior native chickens.